The Turbulent Totality and the Total Experience: Cultural Activities at The Black Diamond, The Royal Library in Copenhagen - Steen Bille Larsen (Liber Quarterly: The Journal of European Research Libraries, 2000)
With this paper I should like to pass on some experiences from The Royal Library in Copenhagen as to how new activities can become part of a new library concept.